The cultural contradictions of capitalism - Bell, Daniel, 1919-2011 (New York : Basic Books, 1996)
"Since its original publication in 1976, The Cultural Contradictions of Capitalism has been hailed as an intellectual tour de force that redefines how we think about the relationship among econmomics, culture, and social change. Daniel Bell, the author of such other modern classics as The End of Ideology and The Coming of Post-Industrial Society, argues that the unbounded drive of modern capitalism undermines the moral foundations of the original Protestant ethic that ushered in capitalism itself. In a major new afterword, Bell offers a bracing perspective on contemporary Western society, from the end of the Cold War to the rise and fall of postmodernism, revealing the crucial cultural fault lines we face as the twenty-first century approaches."--Jacket
t t t t t t
Includes bibliographical references and index
Keywords: United States -- Civilization -- 1945-; United States -- Social conditions -- 1945-; Technology and civilization; Capitalism